A Brief Comparison of Particle Swarm Optimization Algorithm and Firefly Algorithm - Ahmad Sanmorino (Jurnal Informatika Upgris, 2018)
In this article, we try to present some optimization algorithms that are often used by researchers. Through the information contained in this article, the reader can know and understand the development and mechanism of optimization algorithms. The algorithms presented in this article include particle swarm optimization algorithm and firefly algorithm. We chose the swarm particles optimization algorithm and the firefly algorithm to discuss because both of these algorithms are widely used for various optimization problems. Both algorithms, particle optimization algorithms as well as the newer firefly algorithms, are well known today among researchers Furthermore, after knowing the mechanism and the difference of each optimization algorithm, it is expected the reader can choose the algorithm to be used as needed.